What is worth knowing about peritoneal metastases in colorectal cancer? - Stańczak, Michał; Kruszewski, Wiesław; Ciesielski, Maciej; Walczak, Jakub; Kurek, Piotr; Buczek, Tomasz; Szajewski, Mariusz (Frontiers in Surgery, 2026)
Peritoneal metastases (PM) from colorectal cancer (CRC) represent a unique clinical challenge with distinct biological behavior and therapeutic implications. Although PM has traditionally been associated with poor prognosis, recent advances in diagnostics, surgical techniques, and intraperitoneal therapies have offered selected patients opportunities for prolonged survival and, in some cases, long-term disease-free status. This review discusses the pathophysiology, risk factors, diagnostic strategies, and treatment options for CRC patients with PM. The peritoneum is the second most common site of CRC metastasis after the liver, with synchronous and metachronous PM occurring at similar rates. Risk factors include right-sided colon tumors, BRAF mutations, and mucinous histology. Diagnosis relies on imaging modalities such as CT, MRI, PET/CT, and laparoscopy, although sensitivity remains limited for small-volume disease. The peritoneal carcinomatosis index (PCI) is a critical prognostic and therapeutic decision-making tool. Cytoreductive surgery (CRS) with or without hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to improve survival, particularly in well-selected patients with limited PCI and resectable disease. While the role of HIPEC remains debated following the PRODIGE 7 trial, alternative approaches such as pressurized intraperitoneal aerosol chemotherapy (PIPAC) are emerging. Systemic chemotherapy remains foundational, but response in PM can differ from parenchymal metastases due to the peritoneal–plasma barrier. Overall, outcomes are most favorable when patients are managed in specialized centers by multidisciplinary teams offering individualized, biomarker-informed treatment strategies. Ongoing research into molecular predictors and innovative drug delivery methods is critical to further improving prognosis for this complex patient population.